Employee share-ownership plans in the mining industry - a new approach to ESOPS - Diale, Makatane Kagisho Jacob (My University, 2017)
Empowerment of previously disadvantaged groups has been applied in many countries, in order to achieve specific political, economic and social outcomes. Group preferences and preferential policies are common in developed and developing countries under various names. They have been mostly implemented in countries where a specific ethnic, religious, or gender group has been discriminated against historically. An ESOP is an empowerment tool that can be adapted and designed to achieve the goals of companies, employees and governments. An ESOP is an instrument used to enable employee ownership in private and public companies. Internationally the application of ESOPs have taken various architectures highly dependent on individual company and country circumstances. SA has a long and well documented history of racial discrimination and economic exclusion. Poverty, unemployment and inequality continue to bedevil the South African economy. Transformation in the mining industry is given effect in the Mining Charter which is governed under section 100 of the Minerals and Resources Development Act. The Charter is buttressed by a key set of pillars. These pillars are supplemented by the codes of good practice as well as the housing and living conditions standards. These pillars include reporting; ownership; housing and living conditions; procurement and enterprise development; employment equity; human resource development; mine community development; sustainable development and growth and beneficiation. This report focusses on the ownership pillar of the Charter. The mining industry has completed a number of empowerment deals post implementation of the Mining Charter. The impacts of most BEE deals have not been broad-based; and have mostly benefitted only a few HDSA entrepreneurs. The value and number of transactions have coincided with the rise and fall of the JSE, making the deals expensive – due to elevated stock prices in favourable market conditions. ESOPs enable extensive employee ownership; and have the ability to foster a sense of individual enterprise that fuels productivity in companies that have imbued a culture of ownership amongst their employees. ESOPs generally contribute positively to company performance; and they provide a stable and dynamic working environment, when administered effectively. ESOPs cannot be implemented in isolation; but they require a combination of factors to make them successful. ESOPs generally contribute positively to company performance; and they provide a stable and dynamic working environment, when administered effectively. Effective ESOPs require a combination of elements for success: these comprise of financial incentives, employee-involvement mechanisms and the instilling of an ownership culture. Anglo American was used as a proxy for the industry due to its size and diversity. ESOPs that have been implemented have failed to meet stakeholders’ expectations. These ESOPs are inconsistent, complicated and mostly opaque to employees; whilst delivering modest returns to employees. This report proposes the application of a new ESOP framework that is to be considered in amending existing ESOPs or in the crafting of new programmes. Existing ESOPs are assessed against this proposed framework in this report. The proposed ESOP framework is supported by a set of key principles, essential to the success of the framework. The performance of ESOPs in Anglo American varied when assessed against the framework. With the exception of Envision, Anglo American’s ESOPs have delivered very modest financial benefits to employees. They have not achieved their intended purpose, of empowering employees and aligning company performance with individual employee performance. When assessed against the other pillars of the framework, KIO and AAP did not perform satisfactorily.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2017
Keywords: Employee ownership--South Africa; Employee empowerment--South Africa; Mineral industries--South Africa